Strain-specific responses of Pyropia haitanensis to light intensity in growth, carbon content, and organic carbon release - Zhang, Zhongsheng; Wang, Wenlei; Xu, Yan; Ji, Dehua; Xie, Chaotian; Xu, Kai (Frontiers in Marine Science, 2025)
Light strongly influences the carbon (C) metabolism of seaweed through both algal carbon content and organic carbon release, thereby driving the carbon cycling of coastal oceans. However, the response of seaweed organic carbon release to varying light intensities remains an underexplored area of research. This study aimed to fill this gap by analyzing the effects of four different light intensities (5, 50, 200, and 500 μmol m–2 s–1) on the growth, carbon content, and organic carbon release of two strains (W28–42 and WO15-4) of Pyropia haitanensis. The results showed that as light intensity increased, both strains experienced an initial rise in growth rate followed by a decline, with the highest growth observed at 200 μmol m–2 s–1. Simultaneously, tissue C content increased with light intensity, whereas the nitrogen (N) and phosphorus (P) contents exhibited decreasing trends. This led to increases in the C:N and C:P ratios, indicating that high light intensity may enhance C fixation and suppress the absorption of N and P. Of particular interest was the difference in organic carbon release between the two strains. The W28–42 strain’s rate of dissolved organic carbon (DOC) release increased significantly with light intensity, whereas the WO15–4 strain’s DOC release rate remained unaffected by variations in light intensity. The particulate organic carbon (POC) release rates of both strains increased under higher light intensity, with the W28–42 strain showing a more substantial increase than the WO15–4 strain. This study demonstrates that the release of DOC by P. haitanensis exhibits distinct strain-specific responses to variations in light intensity, a result that may be attributed to differences in photosynthetic physiology and genetic makeup. These insights provide a foundation for enhancing the efficiency of fishery carbon sinks through the manipulation of light intensity.